Circuit selectivity in drug versus natural reward seeking behaviors. Issue 5 (13th February 2021) - Nall, Rusty W.; Heinsbroek, Jasper A.; Nentwig, Todd B.; Kalivas, Peter W.; Bobadilla, Ana‐Clara
Abstract: Substance use disorder (SUD) is characterized, in part by behavior biased toward drug use and away from natural sources of reward (e.g., social interaction, food, sex). The neurobiological underpinnings of SUDs reveal distinct brain regions where neuronal activity is necessary for the manifestation of SUD‐characteristic behaviors. Studies that specifically examine how these regions are involved in behaviors motivated by drug versus natural reward allow determinations of which regions are necessary for regulating seeking of both reward types, and appraisals of novel SUD therapies for off‐target effects on behaviors motivated by natural reward. Here, we evaluate studies directly comparing regulatory roles for specific brain regions in drug versus natural reward. While it is clear that many regions drive behaviors motivated by all reward types, based on the literature reviewed we propose a set of interconnected regions that become necessary for behaviors motivated by drug, but not natural rewards. The circuitry is selectively necessary for drug seeking includes an Action/Reward subcircuit, comprising nucleus accumbens, ventral pallidum, and ventral tegmental area, a Prefrontal subcircuit comprising prelimbic, infralimbic, and insular cortices, a Stress subcircuit comprising the central nucleus of the amygdala and the bed nucleus of the stria terminalis, and a Diencephalon circuit including lateral hypothalamus. Evidence was mixed for nucleus accumbens shell, insular cortex, and ventral pallidum. Studies for all other brain nuclei reviewed supported a necessary role in regulating both drug and natural reward seeking. Finally, we discuss emerging strategies to further disambiguate the necessity of brain regions in drug‐ versus natural reward‐associated behaviors. Abstract : We evaluated the literature and propose circuitry necessary for drug but not natural reward seeking. Circuitry is selectively necessary for drug rewards includes an Action/Reward subcircuit: nucleus accumbens core (NAcore), ventral tegmental area (VTA); Prefrontal subcircuit: prelimbic (PL), infralimbic (IL) cortices; Stress subcircuit: central nucleus of the amygdala (CeA), bed nucleus of stria terminalis (BNST); and Diencephalon subcircuit: lateral hypothalamus (LH). Evidence was mixed for nucleus accumbens shell (NAshell), insular cortex (IC), and ventral pallidum (VP). Circuitry is necessary for both drug and natural reward: subthalamic nucleus (STN), basolateral amygdala (BLA), and hippocampus (HIPP). We discuss future strategies to expand this circuitry.